Islamic Symbols on Political Messages in Newspapers in Riau (Study in Regional Head Election 2017) - Muhd Ar. Imam Riauan; Syukur Kholil; Ahmad Thamrin Sikumbang (Budapest International Research and Critics University, 2019)
: This study seeks to find the process of constructing Islamic symbols in the political message of newspapers in Riau. The symbol of Islam in question is a symbol of Islam exposed by newspapers in Riau during the campaign of the regional head election of Pekanbaru City starting from October 26, 2016 to February 11, 2017. The theory used in this study is social construction theory, by Peter L .Berger and Thomas Luckmann. Peter L.erger who at the beginning of his development, this theory is a constructivist study in sociology to understand the interactions created by individuals as members of society in a continuous manner becomes a reality that is experienced together in social life. This research uses a constructivist approach to understand how the process of constructing Islamic symbols in political messages. The subjects of this study were 5 candidates for regional head of Pekanbaru City who were actively exposed by the media and used Islamic symbols in various campaign activities during the Campaign from 26 October 2016 to 11 February 2017. The object of the research was the construction of Islamic symbols exposed to newspaper in Riau. The results of this study indicate that the construction process is divided into two, namely the construction process that occurs because it is caused by the process of finding data and facts about the needs of the community and the construction process that appears as the identity of prospective regional heads.